Participation of women in side-income: a case study of Iban women as a bread-earner in the family in Sarawak - Rosli, Anita; Daud, Adrian; Md Saad, Juniza; Robin, Tunung (Human Resource Management Academic Research Society, 2023)
Nowadays, women also play a role as bread-earners in the family, whether as workforce or part-time workers, due to the increase in living costs. Doing side-income activities among working women and full-time housewives is one of the common ways to earn additional income for the family. Iban ethnic women in Sarawak perform several activities as daily life activities and for additional earnings. This study investigates side-income activities among Iban women in Sarawak. The study will be conducted using survey methods among Iban women participating in side-income activities using simple random sampling, and a total of 325 Iban women participated in the survey. The study's findings show three main side-income activities, i.e., farming, handicraft making, and business. However, respondents need help conducting side-income activities, such as a lack of knowledge and skills in certain fields, problems in marketing and promotional, and financial constraints. Based on the identified problems, three suggestions have been recorded by a high percentage of respondents, i.e., marketing, and promotional assistance, providing business and entrepreneurship courses, and providing financial assistance. Thus, such assistance and pieces of training could support their side-income activities. The side-income earners among Iban women benefit the family, develop Iban society, and encourage Iban women's development and empowerment in Sarawak.